2013
DOI: 10.1261/rna.038869.113
|View full text |Cite
|
Sign up to set email alerts
|

Distinct binding interactions of HIV-1 Gag to Psi and non-Psi RNAs: Implications for viral genomic RNA packaging

Abstract: Despite the vast excess of cellular RNAs, precisely two copies of viral genomic RNA (gRNA) are selectively packaged into new human immunodeficiency type 1 (HIV-1) particles via specific interactions between the HIV-1 Gag and the gRNA psi (ψ) packaging signal. Gag consists of the matrix (MA), capsid, nucleocapsid (NC), and p6 domains. Binding of the Gag NC domain to ψ is necessary for gRNA packaging, but the mechanism by which Gag selectively interacts with ψ is unclear. Here, we investigate the binding of NC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
144
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(166 citation statements)
references
References 79 publications
20
144
2
Order By: Relevance
“…This finding differs from those for HIV-1, for which reports have shown that NC is salt sensitive (51-53), but Gag-facilitated annealing is much less sensitive to salt in this range (20,54). Experiments demonstrating that aggregation of NA by RSV NCp12 is abrogated by increasing concentrations of NaCl are consistent with our observation that the NA chaperone activity of NCp12 was salt dependent (55).…”
Section: Discussionsupporting
confidence: 65%
“…This finding differs from those for HIV-1, for which reports have shown that NC is salt sensitive (51-53), but Gag-facilitated annealing is much less sensitive to salt in this range (20,54). Experiments demonstrating that aggregation of NA by RSV NCp12 is abrogated by increasing concentrations of NaCl are consistent with our observation that the NA chaperone activity of NCp12 was salt dependent (55).…”
Section: Discussionsupporting
confidence: 65%
“…In HIV-1, NC plays a major role at this stage and binds the genome specifically. We have recently shown that HIV-1 Gag binds to psi-specific RNAs differently than to non-psi RNAs; our data suggest that psi binding involves primarily the NC domain, whereas non-psi binding involves both the NC and MA domains (58). In contrast, we propose that in deltaretroviruses, MA plays a larger role in recognizing gRNA at the initial stage.…”
Section: Discussioncontrasting
confidence: 55%
“…Hairpins were also extended after exposure to a solution of NC prepared as described previously (33). The specific binding sites on TAR RNA appear to be saturated at 50 nM NC (34,35), as discussed further in SI Materials and Methods, section 9.…”
Section: Methodsmentioning
confidence: 91%